Inclusiveness of Development – A Challenge for A Post-Pandemic Global Economy - Iwona PAWLAS (Communications of International Proceedings, 2020)
Inclusiveness of development should be a response to exclusion, inequality and injustice in the global economy. The COVID-19 global pandemic strengthened the problem and scale of exclusion. Creating an inclusive post-pandemic global economy would require systemic, organizational and mental changes not only of the society of one or the other country, but of the entire international community. Special circumstances would be necessary for this sort of change, constituting turning points enabling the formation of a new paradigm of development. Author studied, explored and discussed the essence, dimensions and levels of inclusiveness, and then described the factors, instruments, barriers and measures of inclusiveness. Moreover, Author discussed selected studies in the field of inclusiveness undertaken by the authors in recent years and presented selected initiatives launched on international level in order to increase inclusiveness (by the United Nations, Organization for Economic Cooperation and Development, European Bank for Reconstruction and Development and the European Union).
Keywords: inclusiveness; development; global economy; COVID-19 pandemic.